Single photoionization of aluminum-like P2+ and magnesium-like P3+. (July 2015) - Hernández, L.; Covington, A.M.; Hernández, E.M.; Antillón, A.; Morales-Mori, A.; Chartkunchand, Kiattichart; Aguilar, A.; Hinojosa, G.
Abstract: Absolute single-photoionization cross sections for aluminum-like P 2+ have been measured from 26.5 to 66.5 eV using photoion yield spectroscopy. In addition, absolute cross section measurements for the single-photoionization of magnesium-like P 3+ have been measured from 43 to 60 eV. For both ions, the measured spectra are dominated by Rydberg series resonances superimposed on a non-resonant direct photoionization cross section. Analyses of these data have helped identify the initial and final states of the Rydberg series observed in each photoion. In addition, quantum defects are derived for each series. Abstract : Highlights: High resolution ion-yield spectra for the single photoionization of P III and P IV. Absolute cross section measurements for single photoionization of P III and P IV. Resonant Rydberg series superimposed on a non-resonant cross section for both ions. Undetermined populations of metastable states in initial P III and P IV ion beams.